Dramaturgia Michaiła Bułhakowa na współczesnej polskiej scenie. Uwagi o spektaklu Molier. Z urojenia - Gracla, Jadwiga (Acta Polono-Ruthenica, 2018)
In this sketch, the author attempts to analyze the spectacle of the Bialystok group PAPAHEMA created on the basis of the drama Bulgakov Molier, or conspiracy of the saints. In the spectacle, the display of biographical threads for the purpose of universal aim`s has been dispensed with. According to the author, the creator of the spectacle, while remaining faithful to the assumptions of the text, created a universal spectacle, presenting motifs of human behavior and, above all, exposing the theatricality of the text.